A crimson warning eaudiobook Lady emily mysteries series, book 6. - Alexander, Tasha (Lady Emily, 2013)
Best-selling author Tasha Alexander crafts compelling works that are equally celebrated for their intricate plotting and historical authenticity. A Crimson Warning features beloved character Lady Emily Hargreaves, who can usually be found waltzing or reading from the aeneid when not fighting for women's suffrage. Lady Emily's enjoyment of the season, however, comes to an abrupt end when the red paint being splashed on doorsteps heralds ill-even deadly- tidings.